2016
DOI: 10.1177/1535370216654587
|View full text |Cite
|
Sign up to set email alerts
|

Bax-induced apoptosis shortens the life span of DNA repair defect Ku70-knockout mice by inducing emphysema

Abstract: Cells with DNA damage undergo apoptosis or cellular senescence if the damage cannot be repaired. Recent studies highlight that cellular senescence plays a major role in aging. However, age-associated diseases, including emphysema and neurodegenerative disorders, are caused by apoptosis of lung alveolar epithelial cells and neurons, respectively. Therefore, enhanced apoptosis also promotes aging and shortens the life span depending on the cell type. Recently, we reported that ku70(-) (/) (-)bax(-) (/) (-) and k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…It was revealed that expression of the pro-apoptotic protein Bax increased, while the levels of anti-apoptotic proteins, including cIAP1, cIAP2 and Bcl-2 decreased significantly following Rsf-1 depletion, as reported in previous studies (4648); Rsf-1 overexpression induced opposing effects. cIAP1 and cIAP2 are members of the IAP family, which regulate apoptosis and chemoresistance (49).…”
Section: Discussionsupporting
confidence: 80%
“…It was revealed that expression of the pro-apoptotic protein Bax increased, while the levels of anti-apoptotic proteins, including cIAP1, cIAP2 and Bcl-2 decreased significantly following Rsf-1 depletion, as reported in previous studies (4648); Rsf-1 overexpression induced opposing effects. cIAP1 and cIAP2 are members of the IAP family, which regulate apoptosis and chemoresistance (49).…”
Section: Discussionsupporting
confidence: 80%
“…46 XRCC6 protects cells from DNA damage by encoding the protein Ku70, which binds broken DNA ends and represses BAX-induced apoptosis. [47][48][49] Poly (ADP-ribose) polymerase (PARP1) plays crucial roles in repairing DNA damage and facilitating cell cycle progression, follicular development and atresia formation. 50 PARP inhibition also reduces ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Ku70 and Bax were found to interact in the cytoplasm and to inhibit Bax activation [20,64,115,117]. Upon Ku70 knockdown or acetylation, Bax dissociates from the Ku70 complex and translocates to the mitochondria [16,117,118,119]. Overexpression of Ku70 blocks apoptotic cell death induced by transfected Bax [120].…”
Section: Ku70 Regulates Apoptosis-related Proteinsmentioning
confidence: 99%